2012
DOI: 10.3762/bjoc.8.90
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic glycopeptides and glycoproteins with applications in biological research

Abstract: SummaryOver the past few years, synthetic methods for the preparation of complex glycopeptides have been drastically improved. The need for homogenous glycopeptides and glycoproteins with defined chemical structures to study diverse biological phenomena further enhances the development of methodologies. Selected recent advances in synthesis and applications, in which glycopeptides or glycoproteins serve as tools for biological studies, are reviewed. The importance of specific antibodies directed to the glycan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 148 publications
0
24
0
Order By: Relevance
“…[3] These endeavours are not straightforward, and success in rationalizing such processes has been possible only in a handful of well-studied cases. [4] Important insights into such questions have been gleaned from the study of glycoconjugate mimetics, whose interactions with cellular targets can impact a wide range of physiological phenomena, including fertilization, immune response, host–pathogen interactions, cell growth, and tumor metastasis. [1] However, attempts to successfully correlate biological functions of structurally well-defined glycopeptides with their secondary structures have been relatively sparse, [24] despite the importance of such targets in the quest for carbohydrate-based therapeutics.…”
mentioning
confidence: 99%
“…[3] These endeavours are not straightforward, and success in rationalizing such processes has been possible only in a handful of well-studied cases. [4] Important insights into such questions have been gleaned from the study of glycoconjugate mimetics, whose interactions with cellular targets can impact a wide range of physiological phenomena, including fertilization, immune response, host–pathogen interactions, cell growth, and tumor metastasis. [1] However, attempts to successfully correlate biological functions of structurally well-defined glycopeptides with their secondary structures have been relatively sparse, [24] despite the importance of such targets in the quest for carbohydrate-based therapeutics.…”
mentioning
confidence: 99%
“…Several other studies have also demonstrated reduced susceptibility of MRSA against glycopeptide and lipopeptide (Estes and Derendorf, 2010; Judge et al, 2012). The reduced susceptibility of glycopeptide is due to trapping of glycopeptide in the peptidoglycan of the bacterial cell, thus allowing decreased number of glycopeptide reaching the cytoplasmic membrane where the targets of glycopeptides are located (Westerlind, 2012). Nonsusceptibility to daptomycin has also been associated with changes in the structure and function of the cell envelope and surface charge.…”
Section: Discussionmentioning
confidence: 97%
“…289,290 Consequently, efficient methods have been developed for the solid-phase synthesis of peptide thioesters as ligation partners, 215,[291][292][293][294] as well as a number of new reagents, coupling partners, and protocols for carrying out these types of regioselective and racemization-free ligation reactions. 295,296 A number of glycopeptides and glycoproteins have been prepared using this approach, [297][298][299] with larger proteins constructed via sequential ligation of multiple peptide fragments. 300 Desulfurization approaches that enable structural modification of thiol-containing amino acids at the ligation site have also been developed for incorporating amino acids other than cysteine at the ligation site.…”
Section: Ac-tyr( T Bu)thr( T Bu)ser( T Bu)leuilehis(trt)ser( T Bu)leumentioning
confidence: 99%